LOCAL POLITIC DYNAMICS, NATION INTEGRATION AND HISTORY LEARNING CHALLENGE - Iskandar, Israr (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2011)
Even though it is not directly included in the history study material, local politic dynamics in regional autonomy era can also be a challenge for history study at pre-university level. Negative excess of regional autonomy policy implementation and politic development after â€œOrde Baruâ€ era that is likely to challenge the effectiveness of nationalism and national country existence can be a special challenge for history study, and civic education in general. At one side, the comprehensive history teaching will develop contextual nationalism spirit to the youth but at the other side, the phenomenon of regional autonomy implementation and local politic dynamics in the reformation era will challenge the existence of the nationality spirit, due to the spirits emerged and strengthened are the ethnocentrism, ethnicity, social conflict, and separatism. Special strategy for history study at school will be necessary to overcome the issue.